Meanings of Sexuality: Views from Malay Women with Sexual Dysfunction - Muhamad, Rosediani; Horey, Dell; Liamputtong, Pranee; Low, Wah Yun; Sidi, Hatta (Springer, 2019)
In Malaysia, female sexual dysfunction (FSD) among Malays is common, so understanding the meanings of sexuality becomes crucial, as they can vary with identity, and this may influence each woman’s subsequent reaction to sexual experience. In this article, we explore the meanings of sexuality that Malay women had developed throughout their lived experience. This qualitative study, situated within a social cognitive theory and a phenomenological framework, was conducted through in-depth and photograph elicitation interviews with 26 Malay women who had self-reported experiencing FSD. The findings suggest that the meanings of sexuality for these women linked closely with fundamental factors of Malay identity, which is comprised of tradition (Adat), religion (Islam), and language, that all influence gendered roles. Malay women understood sexuality to be sexual intimacy within marriage, privileging their marital role as a “good wife” over their personal rights within a sexual relationship. This understanding of sexuality was reinforced by meanings attributed to procreation, which Malay women linked closely to the purpose of marriage and their role as a “good mother.” The findings should provide useful evidence that could be used in sexual health promotions to help reduce FSD and in clinical practice to generate appropriate therapy in Malaysia and elsewhere. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.